The Influence of Self-Determination on Career Success through Work Engagement: A Study on Startup Employees in Surabaya (International Journal of Innovation and Business Strategy (IJIBS), 2024)
This research aims to analyze the influence of self-determination on career success through work engagement in startup employees throughout Surabaya. This study uses a quantitative approach. The population of this research is startup employees spread across Surabaya and the sample size collected was 124 respondents. The sample collection technique uses an accidental sampling technique. The data in this study were analyzed using SEM-PLS which was processed with SmartPLS 3.2.9 software. The analysis results obtained from this research show that (1) Self-determination has a significant positive effect on career success. (2) Self-determination has a significant positive effect on work engagement. (3) Work engagement has a positive effect on career success. (4) Work engagement can mediate the influence of self-determination on career success. From this research, it can be concluded that self-determination can support career success in startup employees throughout Surabaya and foster work engagement in the work environment at startup companies. So that employees can develop all their ideas, thoughts, and potential which will directly impact the startup company. Apart from that, the model in this research is new so it can be studied further on other objects.
Keywords: Self-Determination; Career Success; Work Engagement